IF IT AIN’T BROKE, IMPROVE IT: THOUGHTS ON ENGAGING EDUCATION FOR US ALL - Gilbert, Steven W. (Online Learning, 2004)
One of the continuing challenges of education is enabling those who strive to improve teaching, learning, and research to take advantage of the too-rapidly-changing new environment created by telecommunications and information technologies. To do so, educational professionals should engage in lifelong professional development and use new hybrid technologies to help build community and support collaboration. This paper explores the issues of technology and professional development from the frame of reference of my work with hundreds of colleges that have benefited from the Teaching, Learning, and Technology Group (TLT Group), an organization whose mission is to motivate and enable institutions and individuals to improve teaching and learning with technology, while helping them cope with change. This article discusses challenges that higher education faces: creating visions worth working toward; developing strategies and tools for achieving intermediate goals; and the importance of breaking taboos along the way.